Kekuatan Eksekutorial Kesepakatan Mediasi Dalam Sistem Peradilan Perdata Indonesia - Hasan Hasan; Munira Munira; Kattya Nusantari Putri (ARBITER: Jurnal Ilmiah Magister Hukum, 2026)
This study aims to analyze the executory power of mediation agreements within the Indonesian civil justice system and to identify the gap between normative regulations and their practical implementation. Mediation, as part of alternative dispute resolution, has been formally integrated into the judicial system through Supreme Court Regulation Number 1 of 2016 concerning Court-Annexed Mediation Procedures. This research employs a normative juridical method using statutory, conceptual, and case approaches. The findings reveal that mediation agreements embodied in a deed of settlement possess the status of a final and binding court judgment (inkracht van gewijsde) and carry executory power equivalent to judicial decisions. However, in practice, the effectiveness of such executory power remains suboptimal due to the absence of standardized execution mechanisms, weak judicial supervision, low compliance of the disputing parties, and uneven mediator competence. This study finds a significant gap between the normative strength and the practical effectiveness of settlement deeds in judicial practice. Therefore, strengthening regulations, improving the professionalism of mediators and judges, and reformulating supervision and execution mechanisms are necessary to enhance legal certainty and the effectiveness of dispute resolution through mediation.